Linked Data Technologies in Libraries: An Appraisal - Nosheen Fatima Warraich (Journal of Political Studies, 2016)
This study aims to explore the information professionals’ insight about the potential benefits of Linked Data application in libraries. It also discussed the basic concepts of LD to create the awareness among information professionals. Linked Data is an emerging set of standards and technologies that could potentially enable information environments such as libraries to publish and interlink their hidden data on the web for better global accessibility. However, it is also one of the least understood phenomena, especially with respect to its adoption and application by libraries. This work is part of a larger study that was designed to investigate perception and application of Linked Data technologies in Pakistani libraries. This is a quantitative study based on a questionnaire survey. To meet the objective of the study, a survey of academic library information professionals was designed and circulated online to collect data from geographically scattered population. This paper found that information professionals perceived that LD has the potential to interlink and publish library data on the Web and it will also assist patrons to discover relevant information through links to other repositories. They were of the view that LD will be useful for library patrons to find content on web and it will supplement the library’s records from online sources. Respondents also opined that LD would improve users’ overall search experiences with existing library catalogs. It is the base line study on Linked Data application in libraries in Pakistani context as no literature available on it. This study provides practical suggestion for decision makers and opens the future research avenues for researchers.